2019
DOI: 10.17977/um016v3i12019p035
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristic of Overhang Object to Material Usage on FDM 3D Printing Technology

Abstract: Fuse Deposition Modeling (FDM) 3D printing is one of additive manufacturing technology which physical 3D model is build up layer by layer. The support structure is almost involved on the process if overhang shape is met on the 3D model. It has main function to prevent the 3D printed model from collapsing. Commonly, the single material source of FDM 3D printer machine is to supply building two structure, structure of main 3D object and support structure. Hence, our goal optimizes the using of support material f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Anderson proposed direct recycling of the applied PLA filament thru its floor up and reextrusion into 3D printing filament. After extrusion cycles and one 3D printing process, the cloth keeps comparable diameter and surface end because the authentic one, even as its mechanical homes exhibit mild deteriorations [7]. Unexpected discount in viscosity, attributed to chain scission at some stage in recycling, is the primary draw-lower back that prohibits subjection of the applied PLA filament to similarly 3D printing [8] As the main component of 3D printing materials are filaments that have been extracted from raw materials that can indeed be used as solid objects.…”
Section: Extrusion Progressmentioning
confidence: 99%
“…Anderson proposed direct recycling of the applied PLA filament thru its floor up and reextrusion into 3D printing filament. After extrusion cycles and one 3D printing process, the cloth keeps comparable diameter and surface end because the authentic one, even as its mechanical homes exhibit mild deteriorations [7]. Unexpected discount in viscosity, attributed to chain scission at some stage in recycling, is the primary draw-lower back that prohibits subjection of the applied PLA filament to similarly 3D printing [8] As the main component of 3D printing materials are filaments that have been extracted from raw materials that can indeed be used as solid objects.…”
Section: Extrusion Progressmentioning
confidence: 99%
“…A layer height of 0.14 mm shows the optimum value for increasing printing speed, and obtaining the appropriate product [9]. Previous study has also investigated the influence of deposition layer to surface quality for self-supporting deposit layer [10]. It shows that the angle 11 o can improve the quality of 3D printed surface.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research showed that a layer height of 0.2 mm showed a relatively low manufacturing time compared to a layer height of 0.15 mm [7], whereas at a layer height of 0.25 mm, the difference in print time was not significant. Apart from that, the vertical orientation of the workpiece print could also slow down the print time [8]. To speed up printing time, low infill density could be used to make printing time efficient, but it could reduce the mechanical properties of the printed product [10].…”
Section: Introductionmentioning
confidence: 99%